The influence of hold regularity on perceptual-motor behaviour in indoor climbing - Button, C.; Orth, D.; Davids, K.; Seifert, L. (European Journal of Sport Science, 2018)
Climbers often train on indoor climbing walls, which are modifiable to simulate features of outdoor climbing environments at different levels of difficulty. The aim of this study was to evaluate the influence of regularity of climbing holds on emergent perceptual-motor behaviours. Skilled climbers performed six repetitions of two topographically similar routes on an indoor climbing wall. One route was composed of 18 different types of hand holds (irregular route), whereas the other route had only two types of hand holds (regular route). Preview and climbing durations, as well as visual search behaviours, were recorded. Participants rated the regular route as more difficult to climb, requiring greater perceived effort to complete. The time spent previewing, and then climbing the routes, was reduced on average by 12% and 16%, respectively in the irregular route compared to the regular route. There were more fixations made when climbing the regular route (281 vs. 222 fixations per trial). It seems the climbers were more careful and thorough in their gaze behaviours with the regular route because of the additional technical demands it presented, whereas the irregular route afforded a more superficial visual exploration with use of more frequent saccades between holds. The findings suggest how irregularity in the environment is exploited by skilled climbers, apparently making the practice context easier to perceive and act in.